(untitled) (Journal of Telenursing (JOTING), 2023)
This study explores the postpartum care experience in mothers who consume rujak and balanga drugs in Banda Neira District. The method used is qualitative research using a phenomenological design. The results of this study indicate that there is research showing that the five themes include; 1) There are physical, psychological, and sexual changes after postpartum care related to culture; 2) There are cultural restrictions such as strenuous activity, food, and sexuality in postpartum care; 3) The cost factor is a reason to consider in choosing postpartum care; 4) Mothers and parents-in-law dominate sources of decision-making for postpartum care related to culture; 5) There is ambivalence in following postpartum care related to culture. This study concluded that the mother’s ability to adapt to the changes in toddlers is very influential in overcoming stunting. The experience of postpartum care for mothers who consume salad and herbal medicine related to culture is influenced by several factors, namely abstinence, which includes: strenuous activity, food taboos, and sexuality. Keywords: Culture; Consumption of Rujak and Balanga Medicine; Postpartum Care